The memory of light - Stork, Francisco X. (Arthur A. Levine Books, an imprint of Scholastic Inc., 2016)
When Victoria Cruz wakes up in the psychiatric ward of a Texas hospital after her failed suicide attempt, she still has no desire to live, but as the weeks pass, and she meets Dr. Desai and three of the other patients, she begins to reflect on the reasons why she feels like a loser compared with the rest of her family, and to see a path ahead where she can make a life of her own.